2021
DOI: 10.1021/acs.inorgchem.1c00169
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effect on the Selective Separation and Complexation of Trivalent Americium and Lanthanides by N,O-Hybrid 2,9-Diamide-1,10-phenanthroline Ligands in Ionic Liquid

Abstract: The extraction and complexation of trivalent americium (Am) and lanthanides (Ln) by four 2,9-diamide-1,10-phenanthroline (DAPhen) ligands with different alkyl substituent groups on the diamide moiety in an ionic liquid (IL), C 4 mimNTf 2 , were studied through a combination of batch extraction, spectroscopic, and calorimetric approaches. All four DAPhen ligands can achieve selective separation of Am(III) from Eu(III), but the detailed extractability and the extraction kinetics are affected significantly by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Using these ligands permits reaching high selectivity factors SF­(Am 3+ /Eu 3+ ) ≥ 50 for a model pair of Am 3+ /Eu 3+ . The effect of structural modifications of the amide groups of ligands (Figure ) with respect to the extraction properties of Ln and MAn has been studied in several works. , It has been shown that symmetric N,N,N′,N′-tetraalkyl-1,10-phenanthroline-2,9-dicarboxamides (Figure ; R 1 = R 2 = Et, n -Bu, n -Hex, n -Oct; X = H) are less efficient in their extraction ability with respect to actinides than Et-Tol-DAPhen …”
Section: Introductionmentioning
confidence: 99%
“…Using these ligands permits reaching high selectivity factors SF­(Am 3+ /Eu 3+ ) ≥ 50 for a model pair of Am 3+ /Eu 3+ . The effect of structural modifications of the amide groups of ligands (Figure ) with respect to the extraction properties of Ln and MAn has been studied in several works. , It has been shown that symmetric N,N,N′,N′-tetraalkyl-1,10-phenanthroline-2,9-dicarboxamides (Figure ; R 1 = R 2 = Et, n -Bu, n -Hex, n -Oct; X = H) are less efficient in their extraction ability with respect to actinides than Et-Tol-DAPhen …”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids are promising “green” solvents for the Am-selective extraction. However, the high viscosity of these compounds compared to that of molecular solvents presents a limitation for the use of these diluents (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…30−33 In the presence of ionic liquid serving as a diluent, the complexation between f-elements and diamide derivatives based on the phenanthroline occurs by the cation-exchange mechanism with the formation of ML 2 complexes, where M� f-element and L�N,O-donor extractant. 31,32 However, the use of ionic liquid as a diluent in the chemical technology is hampered by the high viscosity, 28 high aqueous solubility (enhanced in the presence of nitric acid), and difficulties in degradation before disposal, 26 there is a slow rate of equilibrium establishment in two-phase systems. 30−33 Additionally, this type of diluent can be more harmful to humans than molecular solvents, 26 and the status of IL's as green solvents has been questioned.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advantages of these ligands are high oxidative, hydrolytic, and radiation stability and high selectivity in binding cations of f-elements (lanthanoids and actinides). These advanced features open real prospects for their use as extractants for the separation of f-elements, which is one of the most difficult tasks in modern nuclear fuel cycle technologies. The most extensive radiochemical process is the PUREX process, in which uranium and plutonium are separated from nitric acid solutions of spent nuclear fuel (SNF). In addition, uranium concentration and purification operations accompany the entire path from ore to nuclear fuel and further SNF reprocessing. Research continues to improve hydrometallurgical technologies for uranium handling.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the complex nature allows to identify the driving force of solvent extraction, as well as to influence the efficiency and selectivity of this process. , The extraction of trivalent f-elements from nitric acid solutions has been described in relative detail for diamides of N -heterocyclic acids. The combination of indirect methods to study complexes in solutions (IR, NMR, UV–vis) and structural research in the solid state (XRD) show that complexes with tetradentate ligands are formed with ligand to metal ratio = 1:1 and 2:1. ,, , An interesting example is the extrusion of one NO 3 – into the outer sphere in the case of the {[La­( L ) 2 (NO 3 ) 2 ] + NO 3 – } complex ( L = N 2 , N 9 -Diethyl- N 2 , N 9 -bis­(4-ethylphenyl)-1,10-phenanthroline-2,9-dicarboxamide) . In the case of Lu­(NO 3 ) 3 phenanthroline, 1:1 complex coordination number reduction was observed from 10 to 9 due to lanthanoid contraction. , …”
Section: Introductionmentioning
confidence: 99%